2016
DOI: 10.1038/srep29971
|View full text |Cite
|
Sign up to set email alerts
|

The impact of preconceptional obesity on trajectories of maternal lipids during gestation

Abstract: Growing challenges of maternal obesity necessitate to focus metabolic management on alternative factors than glycaemia. The objective is to assess longitudinal changes in lipids and inflammatory parameters during pregnancies stratified by pregestational BMI. Therefore, 222 pregnant women (normal-weight BMI < 25: n = 91 (41%), overweight BMI 25–29.9: n = 69 (31%), obese BMI ≥ 30: n = 62 (28%)) underwent a detailed metabolic characterization including fasting lipids and glucometabolic parameters at <21st gestati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
29
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 27 publications
10
29
0
3
Order By: Relevance
“…This longitudinal study was conducted prospectively at the Department of Internal Medicine III, Division of Endocrinology and Metabolism, Unit of Gender Medicine, Medical University of Vienna, between 2010 and 2014 as previously reported in [ 12 , 13 ]. Study participants were recruited among pregnant women attending our diabetes and pregnancy outpatient clinics at a tertiary care center ≤ 21st week of gestation (GW, visit 1) for the assessment of glucose tolerance and were reevaluated during further clinical follow-up periods: 24th–28th GW (visit 2), 30th–34th GW (visit 3), and >36th GW (visit 4) as well as 8–12 months after pregnancy (visit 5).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This longitudinal study was conducted prospectively at the Department of Internal Medicine III, Division of Endocrinology and Metabolism, Unit of Gender Medicine, Medical University of Vienna, between 2010 and 2014 as previously reported in [ 12 , 13 ]. Study participants were recruited among pregnant women attending our diabetes and pregnancy outpatient clinics at a tertiary care center ≤ 21st week of gestation (GW, visit 1) for the assessment of glucose tolerance and were reevaluated during further clinical follow-up periods: 24th–28th GW (visit 2), 30th–34th GW (visit 3), and >36th GW (visit 4) as well as 8–12 months after pregnancy (visit 5).…”
Section: Methodsmentioning
confidence: 99%
“…At each visit, an additional venous blood sample was drawn in fasting condition for further laboratory analysis. Herein, total adiponectin and leptin were measured in duplicates using radioimmunoassay (RIA) purchased from Millipore, Billerica, MA [ 12 , 13 ].…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, obese women demonstrate reduced insulin sensitivity from an earlier gestation, particularly with regard to lipid metabolism [1]. Using non-NMR methods, others have reported dyslipidaemia in obese vs normal-weight pregnancy, including raised total and LDL-cholesterol, lower HDLcholesterol and raised triacylglycerols from the first trimester [24][25][26][27]. The exaggerated dyslipidaemia in obese women prior to and at the time of diagnosis of GDM in the present study suggests exaggeration of these metabolic processes, reflecting enhanced insulin resistance in adipose tissue and reduced suppression of lipolysis [28].…”
Section: Discussionmentioning
confidence: 99%
“…Changes in lipids and lipoproteins could be the result of increased maternal hormone concentrations and other maternal factors, such as prepregnancy BMI and gestational weight gain. [24][25][26][27] Diareme et al 28 reported that the rate of changes in individual plasma lipids varied during normal pregnancy, with triglycerides showing the largest increase and HDL-C the smallest. Similar to previous reports, 24 we observed an initial slow slope in the increase of triglyceride concentrations in the first trimester, followed by a large increase towards the second trimester and doubled concentrations in the third trimester, although not all triglyceride concentrations in the present study were measured in fasting samples.…”
Section: Casesmentioning
confidence: 99%